Porewater evidence of metal (Cu, Ni, Co, Zn, Cd) mobilization in an acidic, ombrotrophic bog impacted by a smelter, Harjavalta, Finland and comparison with reference sites - Rausch, Nicole; Ukonmaanaho, Liisa; Nieminen, Tiina M.; Krachler, Michael; Shotyk, William (Environmental science & technology, 2005)
Porewaters were collected from three Finnish peat bogs subjected to varying inputs of atmospheric trace metals:  Hietajärvi (HIJ), a low-background site, Outokumpu (OUT), near a Cu−Ni mine, and Harjavalta (HAR), near a Cu−Ni smelter. Samples for metal analyses were collected at depths ranging from 10 to 70 cm using a purpose-built syringe-type sampler. Metal concentrations were determined using inductively coupled plasma-sector field-mass spectrometry (ICP-SF-MS). Porewater concentrations at HIJ and OUT (Cd <0.3 nM, Co <1.4 nM, Cu, Ni <8 nM, Zn <250 nM) are independent of metal concentrations in the solid phase (peat). At OUT there is a limited release of Ni to the porewaters, but concentrations in the aqueous phase are generally below 0.3% of the total concentration in any given peat sample. These data are consistent with the immobility of these metals after deposition from the air. In contrast, porewaters at HAR are enriched in trace metals compared to the other sites by a factor of 2 (Zn), 10 (Cd), 20 (Co), and 100 (Cu and Ni) with dissolved fractions of Cu and Ni accounting for ca. 20% of the metal inventories in the cores. The elevated release of metals from solid phases at HAR is consistent with the postdepositional migration of metals at this site and reflects the predominance of oxide phases supplied to the bog surface and the much lower pH values (<3.4). The elevated proton concentrations not only promote mineral dissolution but also compete with cation exchange processes and hinder the formation of metal complexes with organic ligands.